Profil Aktivitas Fisik dan Perilaku Sendentary Mahasiswa Saat Pandemi COVID-19 Di Pulau Jawa - Sofia Dwi Meilina; Donny Ardy Kusuma (Jurnal Sporta Saintika, 2022)
The spread of COVID-19 in Indonesia in these 3 months has experienced a significant increase. The pandemic or what people call it COVID-19 has far-reaching implications for public health. In March 2020, the World Health Organization (WHO) announced that the new coronavirus disease was spreading very quickly as a pandemic. COVID-19 has had a considerable impact, including sedentary behavior and poor levels of physical activity. It has been demonstrated in multicontinental studies (n= 1047) among adults that during the COVID-19 pandemic, daily sitting time increased by 28.6% and the frequency and duration of physical activity decreased by 24% and 33.5%, respectively. This research method uses google survey surveys on all students in Java, who incidentally are still listed as active students in lectures. So that the survey results given can be used as a description of the physical activity and sedentary behavior of all students. This survey was conducted on October 20, 2021 until November 10, 2021. From the results of the survey taken, it will be processed in Excel using the calculation of the IPAQ formula. The results of the survey using the IPAQ questionnaire were analyzed using descriptive analysis using the SPSS application. The results obtained on active students in Java with an average age range of 21 years are still quite good in doing physical activity, as many as (4%) by doing light physical activity, (95%) doing moderate physical activity, and (16%) do strenuous physical activity. often sedentary behavior (63.72%) and the rest have rare sedentary behavior (52.92%).